Pulmonary drug delivery : advances and challenges - Nokhodchi, Ali; Martin, Gary P., 1954- (Chichester, United Kingdom ; Hoboken, NJ : Wiley, 2015)
Drug therapy via inhalation route is at the cutting edge of modern drug delivery research. There has been significant progress on the understanding of drug therapy via inhalation products. However, there are still problems associated with their formulation design, including the interaction between the active pharmaceutical ingredient(s) (APIs), excipients and devices. This book seeks to cover some of the most pertinent issues and challenges of such formulation design associated with industrial production and desirable clinical outcome.
Lung anatomy and physiology and their implications for pulmonary drug delivery / Lucila Garcia-Contreras, Mariam Ibrahim and Rahul Verma -- The role of functional lung imaging in improvement of pulmonary drug delivery / Stephen Dubsky and Andreas Fouras -- Contemporary review of pulmonary delivery : recent advances and continuing challenges / Robert O. (Bill) Williams III and Simone Raffa Carvalho -- Pulmonary drug delivery to the paediatric population : a state of the art review / Marie-Pierre Flament -- Formulation strategies for pulmonary delivery of poorly soluble drugs / Christophe Duret, Nathalie Wauthoz and Karim Amighi -- Lipidic micro and nanoparticles for pulmonary drug delivery : a state of the art review / Hamed Hamishekar, Yahya Rahimpour and Ali Nokhodchi -- Chemical and compositional characterization of lactose as a carrier in dry powder inhalers / Rim Jawad, Gary Martin and Paul Royall -- Particle engineering for improved pulmonary drug delivery through dry powder inhalers / Waseem Kaialy and Ali Nokhodchi -- Impact of particle surface roughness on dry powder inhaler performance / Bernice M J Tan, Celine V Liew, L W Chan and Paul W S Heng -- Dissolution : a critical performance characteristic of inhaled products / Ben Forbes1 and Francesca Buttini -- Drug delivery strategies for pulmonary administration of antibiotics / Paolo Colombo, Anna Giulia Balducci, Ruggero Bettini and Francesca Buttini -- Molecular targeted therapy of lung cancer : challenges and promises / Jaleh Barar, Yadollah Omidi, and Mark Gumbleton -- Defining and controlling blend evolution in inhalation powder formulations using a novel colorimetric method / David Barling, David Morton and Karen Hapgood -- Polymer-based delivery systems for the pulmonary delivery of macromolecules / Nitesh Kunda, Iman M. Alfagih, Imran Saleem and Gillian A. Hutcheon -- Quality by design : concept for the product development of dry powder inhalers / Al-Sayed Sallam, Sami Nazzal, Hatim Al Khatib and Nabil Darwazeh -- Future patient requirements of inhalation devices : the balance between patient, commercial, regulatory and technical requirements / Orest Lastow.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Drug delivery systems; Pulmonary pharmacology; MEDICAL -- Pharmacology; Drug delivery systems; Pulmonary pharmacology; Electronic books; Electronic books